Accounting Information and Managerial Decision Making in the Manufacturing Industry in Nigeria - Lawal, Babatunde (Advances in Social Sciences Research Journal, 2019)
In the contemporary business world, the role of accounting information in making or marring a business cannot be overemphasized. Recent worldwide advances in manufacturing technologies have brought about a metamorphosis in industry. This paper established the relationship between accounting information and managerial decision making in the manufacturing industry in Nigeria. The study was guided by the following research objectives; to establish the relationship that exists between accounting information and production decisions; to evaluate the relationship that exists between accounting information and human resource management decisions and to assess the relationship that exists between accounting information and marketing decisions in the Nigerian manufacturing sector. The research design adopted for this study is the survey design. The population of the study comprised of the eight companies in beverage sector of the manufacturing industry in Nigeria. The survey research made use of Seven Up Bottling Company Plc, and Nigeria Bottling Company as representatives of the manufacturing industry. Primary data was collected through administering of questionnaire to the staff of the companies. The sample size of the study was 382 derived from the Yaro Yamani’s formula. Based on the findings, it was concluded that accounting information has an effect on managerial decision making in the Nigerian manufacturing industry. The study recommended that due to the importance of human capital in any organisation, promotion, transfer and retrenchment decisions should be handled with utmost sensitivity. Also, accounting information should therefore be inculcated into the taking of such decisions as it will affect the human resource management department and the organisation as a whole if the wrong decision is taken.